Krankenhausversorgung im Wandel - Chancen und Risiken für die Labormedizin/Hospital care in times of change: risks and rewards for laboratory medicine. - Neubauer, Günter (Journal of Laboratory Medicine / Laboratoriums Medizin, 2012)
Owing to the huge demographic challenge in terms of a considerable restructuring of the employed workforce, hospital care has changed and thus laboratory medicine underlies increased rationalization pressure. Management solutions include internal process optimization, procurement management, service outsourcing and development of regional networks. Laboratory medicine must realize these solutions, particularly with reference to quality assurance, to remain competitive in the future.